Bacillus thuringiensis Suppresses the Humoral Immune System to Overcome Defense Mechanism of Plutella xylostella - Li, Shuzhong; Xu, Xiaoxia; Shakeel, Muhammad; Xu, Jin; Zheng, Zhihua; Zheng, Jinlong; Yu, Xiaoqiang; Zhao, Qian; Jin, Fengliang (Frontiers in Physiology, 2018)
Background:Plutella xylostella has become a notorious pest of cruciferous crops all over the world. Delta-endotoxins of Bacillus thuringiensis are widely used insecticidal proteins for controlling P. xylostella. However, the interaction mechanism of B. thuringiensis with the immune system of P. xylostella, at the genomic level, is still unclear. This study explored the immune response of P. xylostella to B. thuringiensis, at different time intervals, 6 h, 12 h, 18 h, 24 h, and 36 h, by using RNA-Sequencing (RNA-Seq) and RT-qPCR. Results: In total, 167 immunity-related genes were identified and placed into different families, including pattern recognition receptors (PRRs), signal modulators, immune pathways (Toll, IMD, and JAK/STAT), and immune effectors. It is worth mentioning that the analyses of the differentially expressed immunity-related genes revealed that most of the differentially expressed genes (DEGs) (87, 56, 76, 67, and 73 genes) were downregulated in P. xylostella following B. thuringiensis oral infection at 6 h, 12 h, 18 h, 24 h, and 36 h. Interestingly, our RNA-Seq analysis also revealed reduced expression of antimicrobial peptides, that play a vital role in the humoral immune system of P. xylostella. Conclusion: This study demonstrates that B. thuringiensis plays a novel role in controlling P. xylostella, by suppressing the immune system.